1994
DOI: 10.1063/1.111603
|View full text |Cite
|
Sign up to set email alerts
|

2.7–3.9 μm InAsSb(P)/InAsSbP low threshold diode lasers

Abstract: Lasing has been obtained in the wavelength range 2.7–3.9 μm in double heterostructure diode lasers with an active region made of InAs alloys. The devices were grown by liquid-phase epitaxy. Typical values of threshold current at 80 K were as low as 40 mA and the maximum operating temperature was 180 K. The blue shift of lasing modes was observed with current. This was explained by the increase of the carrier density in the active region above threshold due to intervalence band absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Nonetheless, there are actually only a few reports of detailed optical characteristics from this alloy. In addition, in these previous studies, the epitaxy growth of InAsPSb was performed outside the extent of the miscibility gap by liquid-phase epitaxy (LPE) [2,6,7] or organometallic vaporphase deposition (OMVPE) [3][4][5]. The studies reported here focused on the growth of InAsPSb thick epitaxial layers matched to InAs by gas source molecular beam epitaxy (GSMBE).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there are actually only a few reports of detailed optical characteristics from this alloy. In addition, in these previous studies, the epitaxy growth of InAsPSb was performed outside the extent of the miscibility gap by liquid-phase epitaxy (LPE) [2,6,7] or organometallic vaporphase deposition (OMVPE) [3][4][5]. The studies reported here focused on the growth of InAsPSb thick epitaxial layers matched to InAs by gas source molecular beam epitaxy (GSMBE).…”
Section: Introductionmentioning
confidence: 99%
“…Lasers for 3-4 m can be made from InAs related compounds. 13 The development of technologies for the production of lasers operating at 3.3-3.6 m region provide very attractive tunable radiation sources with relatively high spectral purity. 14,15 The quality of the laser is determined by its spectral characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The random deviations of the fre− quency μ are responsible for the effective width of the lasing line. In view of the Lorentzian shape of the line [16], Df can be found as the doubled standard deviation of the lasing frequency…”
Section: Theoretical Background Of Spectral Linewidth Measurementmentioning
confidence: 99%
“…Lasers for 3-4 μm can be made from InAs related com− pounds [16]. The development of technologies for the pro− duction of lasers operating at 2.3-3.6−μm region provides very attractive tunable radiation sources with relatively high spectral purity [17,18].…”
Section: Introductionmentioning
confidence: 99%